Hydrological characterisation of Ria de Aveiro, Portugal, in early summer - Dias, J. M. (1999)
The hydrological features of Ria de Aveiro, a coastal lagoon on the northwest Atlantic coast of Portugal, were investigated in two sampling surveys carried out between 3/6 and 24/6/97 and between 29/6 and 7/7/97, respectively. There was a significant freshwater inflow into the lagoon during the first survey, especially in the first days, due to the recent rainfalls. Records concerning water level, salinity, temperature and current velocity were performed at several stations located along the four main channels of the lagoon. The type of tide at the mouth was determined and was observed that astronomical tide is the main forcing agent driving water circulation in Ria de Aveiro. The tide at the mouth is semidiurnal and the tidal wave propagation in the lagoon has the characteristics of a damped progressive wave. Typical estuarine longitudinal salinity and temperature gradients connected with the distance to the mouth were identified, whereas vertical and transverse gradients were found unimportant, except in the frontal zone between oceanic and fresh water masses. According to the results, even though Ria de Aveiro should be considered as vertically homogeneous, some channels may reveal characteristics of a partially mixed estuary, depending on the freshwater input.